Advancing GIS-based suitability analysis of BtX, PtX, PBtX, and eBtX facilities using the fuzzy analytic hierarchy process - Marcel Dossow; Mengxi Chen; Hartmut Spliethoff; Sebastian Fendt (MethodsX)
To address the urgent need for sustainable fuel production, this study proposes a novel methodology that integrates Geographic Information Systems (GIS) and Multi-Criteria Decision Analysis (MCDA) techniques to identify optimal sites for Biomass-to-X (BtX), Power-to-X (PtX), or hybrid (e-/PBtX) facilities. The proposed methodology provides a systematic and quantitative approach to evaluate location suitability, offering valuable insights for spatial decision-making in sustainable fuel production from BtX, PtX, or e-/PBtX.The CES-GIS-SAFAHP methodology uses selected and relevant geospatial data, which is processed to derive criteria-specific datasets, such as spatially resolved energy density maps for biomass-based systems and combined wind and solar energy datasets for hybrid processes. These data are then subjected to a Fuzzy Analytic Hierarchy Process (FAHP), which involves the use of pairwise comparisons and Fuzzy normalization to assign weights to the criteria, ultimately resulting in the generation of weighted overlay maps. The results of both the weighed overlay and a concurrently performed exclusion analysis, delineating areas that fail to meet key conditions or constraints, are combined to produce a final suitability map enabling the identification of optimal plant locations based on their overall suitability index. The proposed approach offers a robust, quantitative framework for spatial optimization in the siting of sustainable fuel production facilities with significant applications for policy-makers, industry, and researchers involved in BtX, PtX, and e-/PBtX scale-up.The methodology encompasses a comprehensive suitability analysis, … • Providing a recommended list of suitability and exclusion criteria, categorized into ``requisite,'' ``infrastructure,'' and ``environmental'' criteria, tailored for sustainable fuel production site selection. • Offering a structured workflow for deriving suitability maps through a combination of GIS-based FAHP with exclusion analysis. • Providing a practical, replicable algorithm that can guide users through the process, making it easier to apply in various geographic and project contexts.